Single-cell sequencing reveals cell heterogeneity and aberrantly activated pathways associated with microvascular invasion in hepatocellular carcinoma - Cui, Jianwei; Zeng, Fanyi; Tang, Ming; Yin, Shiwu (Frontiers in Cell and Developmental Biology, 2025)
IntroductionHepatocellular carcinoma (HCC) is the most common primary liver cancer, with microvascular invasion (MVI) identified as a major predictor of early recurrence. However, the intratumor cellular heterogeneity of MVI, the identification of pertinent biomarkers, and the role of intercellular signalling interactions in MVI progression are unclear. This study aims to explore these aspects using single-cell transcriptomic analysis.MethodsThe present study utilized single-cell transcriptomic data from public databases to conduct an in-depth transcriptome analysis of tumour tissues and adjacent nontumor tissues from five patients with hepatocellular carcinoma, with a particular focus on samples from three patients exhibiting microvascular invasion. Bioinformatics tools were employed to analyze gene expression patterns and signalling pathways.ResultsThe findings indicated that MVI-positive malignant cells activate multiple signalling pathways to facilitate invasion and metastasis. Specific malignant cell subtypes strongly associated with MVI were identified, exhibiting distinctive gene expression patterns related to proliferation, invasion, and metabolic reprogramming of tumour cells. Further analysis revealed that the laminin and VEGF signalling pathways are crucial for remodelling the tumour microenvironment and angiogenesis associated with MVI. The MARCKSL1 gene was predominantly expressed in MVI-positive malignant cells and may contribute to MVI progression by interacting with the PTN signalling network. Additionally, MARCKSL1 is linked to tumour resistance to multiple anticancer drugs.DiscussionThis study sheds light on the molecular characteristics and functional heterogeneity of MVI-associated malignant cell subpopulations. The single-cell transcriptome and bioinformatics analyses provided insights into the mechanisms driving MVI, potentially aiding the development of targeted diagnostic and therapeutic strategies. Future research should further validate the role of MARCKSL1 in MVI progression and explore its potential clinical applications.